Succession Dilemma: Power of Perception, Transition Courage, and Assuming the Helm - Wongso, Nikolas; Padmalia, Metta (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Succession process is one of the greatest challenges involved in the continuanceof family businesses through generations. Incumbent reluctance to step down isone of the most prevalent challenges, which can prevent successors fromreplacing incumbents accordingly. This study aims to examine the impact ofperceived business performance on successor willingness to step in, the impactof successor willingness to step in on incumbent willingness to step down, andthe mediating role of successor willingness in the relationship betweenperceived business performance and incumbent willingness to step down. Thisstudy utilizes the quantitative approach with the data collected through 182respondents that include incumbents, successors, or a combination of the two infamily businesses. Data analysis was carried out using the Partial LeastSquares-Structural Equation Modeling (PLS-SEM). Results indicate thatperceived business performance has a significant, positive impact on successorwillingness to step in. Additionally, successor willingness has a significantimpact on incumbent willingness to step down. Analysis establishes successorwillingness to step in to mediate the relationship between perceived businessperformance and incumbent willingness to step aside. These findings can behelpful to enhance succession planning, leadership replacement strategies, andsustainability of family businesses.